Effect of cultivar and seed rate on weed infestation and crop performance of wheat - Halder, PK; Salim, M; Paul, SK (Progressive Agriculture, 2016)
An experiment was carried out at the Agronomy Field laboratory of Bangladesh Agricultural University, Mymensingh during the period from November 2014 to March 2015 to study the effect of cultivar and seed rate on weed infestation and crop performance of wheat. Three wheat cultivars viz. BARI Gam 24, BARI Gam 25 and BARI Gam 26 and five seed rates viz. 80, 90, 100, 110 and 120 kg ha-1 were considered as the experimental treatment. The experiment was carried out in Randomized Complete Block Design with three replications. The cultivar and seed rate were significantly influenced on weed infestation and crop performance of wheat. The dry weight of weeds in cultivar BARI Gam 26 was the lowest (9.24 g m-2) compared to other cultivars. The lowest dry weight of weed was recorded in the seed rate of 120 kg ha-1 (7.57 g m-2) and the highest one (16.14 g m-2) was produced in seed rate of 80 kg ha-1. The highest plant height (93.27 cm), number of effective tillers plant-1 (3.69) and 1000-grain weight (44.51g) were produced in BARI Gam 25. The highest number of spikelet spike-1 (18.12) and grains spike-1 (34.51) were produced by BARI Gam 26. BARI Gam 26 produced the highest grain yield (2.51 t ha-1) which was as good as BARI Gam 25 (2.48 t ha-1). BARI Gam 26 produced the highest grain yield with 100 kg seed rate and also a good competitor against weeds. Seed rate was a reliable factor where increasing seed rate reduced the weed dry weight production. In conclusion, cultivation of BARI Gam 26 @100 kg ha-1 seeds may be cultivated for higher grain yield. Progressive Agriculture 27 (1): 20-26, 2016